Konsep Ilmu dalam Islam: Perspektif Worldview Islam - Murtadho, Imam; Mujahid, Kasori (TSAQOFAH, 2025)
This article examines the concept of knowledge in Islam from an Islamic worldview perspective that offers a holistic and integrative approach. In Islam, knowledge not only functions as a means of understanding the world, but also as a form of worship that brings oneself closer to Allah and contributes to the benefit of the people. Integration between science and ethical values is an important basis for responding to the moral and spiritual crisis faced by modern science. This article also highlights the importance of education based on an Islamic worldview and the application of Islamic values in the development of knowledge as a strategic effort to build a sustainable and ethical civilization. By using the Islamic worldview as a guide, knowledge not only provides material benefits but also blessings for humanity and the universe. This research aims to emphasize the relevance of the concept of science in Islam in facing the challenges of modern science, while at the same time contributing to the development of a civilization based on Islamic values.